2023
DOI: 10.1371/journal.pone.0292722
|View full text |Cite
|
Sign up to set email alerts
|

Modelling arts professionals’ wellbeing and career intentions within the context of COVID-19

Neta Spiro,
Caitlin Shaughnessy,
George Waddell
et al.

Abstract: The COVID-19 pandemic had a substantial effect on the creative and cultural industries in the United Kingdom (UK), as seen in our first snapshot of the HEartS Professional Survey (April–June 2020, Phase 1, N = 358). By analysing data collected one year later (April–May 2021, Phase 2, N = 685), the aims of the current study are to trace the contributors to (1) arts professionals’ mental and social wellbeing and (2) their expectations of staying in the arts. Findings show that artists continued to experience cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Being aware of your emotional journey will not only assist your personal development but will make you more empathetic to students and collaborators. One study showed not only the importance of mental health and well-being for arts careers but demonstrated that physical exercise was positively associated with artists' well-being (Shaughnessy 2023).…”
Section: The Platform Career: One Solution To Reduce Precaritymentioning
confidence: 99%
“…Being aware of your emotional journey will not only assist your personal development but will make you more empathetic to students and collaborators. One study showed not only the importance of mental health and well-being for arts careers but demonstrated that physical exercise was positively associated with artists' well-being (Shaughnessy 2023).…”
Section: The Platform Career: One Solution To Reduce Precaritymentioning
confidence: 99%